2020
DOI: 10.21203/rs.3.rs-83582/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of equine antisera with high neutralizing activity against SARS-CoV-2

Abstract: The pandemic of COVID -19 caused by SARS-CoV-2 is leading to a humongous impact on the mankind with over a million people succumbing to it worldwide. Although there are few drugs approved for the treatment, there is not yet a safe and effective vaccine available for COVID-19. Also, the passive immunization therapy with convalescent plasma, though potentially an effective treatment option for other viral disease has limitation of availability. The prior use of immunoglobulins generated in animals has proven to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…SARS-CoV-2 inactivated by gamma rays was used to inoculate horses (n: 10, Age: 4-10 years) and highly neutralizing antibody titers were detected by ELISA and the purity was checked by SDS-PAGE [30]. The purity of the antisera was determined to be 99% with a neutralizing titer of over 20000 [30]. This study also supports our findings and promises effective results for neutralizing the SARS-CoV-2 in vivo in vivo.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…SARS-CoV-2 inactivated by gamma rays was used to inoculate horses (n: 10, Age: 4-10 years) and highly neutralizing antibody titers were detected by ELISA and the purity was checked by SDS-PAGE [30]. The purity of the antisera was determined to be 99% with a neutralizing titer of over 20000 [30]. This study also supports our findings and promises effective results for neutralizing the SARS-CoV-2 in vivo in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…Convalescent plasma titer level is found to be acceptable at 1:160 by The Food and Agriculture Organization (FAO), and 1:80 when it is not available. SARS-CoV-2 inactivated by gamma rays was used to inoculate horses (n: 10, Age: 4-10 years) and highly neutralizing antibody titers were detected by ELISA and the purity was checked by SDS-PAGE [30]. The purity of the antisera was determined to be 99% with a neutralizing titer of over 20000 [30].…”
Section: Discussionmentioning
confidence: 99%
“…The inherent complexity of these therapeutic agents, due to their polyclonal nature, should be considered. Most work in the field of anti-COVID-19 immunotherapeutics based on HHP antibodies or their fragments has been focused on developing high NtAb titers in naïve animals [ 10 , 11 , 12 , 13 , 14 ]. Additionally, these reports describe the effect of initial hyperimmunization cycles on limited groups of at most five animals.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperimmunized horses’ plasma (HHP) is the starting material for EpAbs production. During HHP production, horses are hyperimmunized with inactivated SARS-CoV-2 virions or selected viral subunits in order to achieve high titers of neutralizing circulating antibodies [ 10 , 11 , 12 , 13 , 14 ]. The Spike protein of Coronaviruses, a complex homotrimeric membrane-protein, is central to host-cell attachment and invasion [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Zylberman et al [ 152 ], the results of the in vitro neutralization tests were 1:10.240 (complete neutralization dilution) of the titer and 30 mg mL −1 of protein in the final product, concluding that it was 50 times the neutralizing potency of the convalescent serum used as a control [ 152 ]. The results obtained by Pan et al [ 158 ] revealed that the neutralization rate for SARS-CoV-2 was greater than 90% by treatment with F(ab’) 2 at a concentration of 31,15 μg mL −1 and more than 50% at a concentration of 7,81 μg mL −1 Sapkal et al [ 159 ] used SARS-CoV-2 inactivated by gamma radiation to prepare the antigen, which generated a final product with neutralizing titers of PRNT90 above 20.000.…”
Section: Immunotherapies Testsmentioning
confidence: 99%